Between Absolute and Fluid Space: the Representation of the Oasis (diségno, 2019)
At the edge of the desert, near the wetlands, the palm grew in small wild spots that reproduced by the action of the wind, forming a favorable environment for human settlement.The landscape of the oasis is a composition of natural elements whose combination transforms the place into artificial nature; the water, the knowledge of agricultural techniques together with hard daily work overwrite to the arid deseret ground the traces of site configuration.The oasis is a homogeneous system structured in the repetition of the elements of which it is composed and which generates a figurative unit given by the neatly arranged parts. A homogeneous plant mass that becomes a defined and balanced system.The image of the oasis is built between the space of the desert, in which there is no presence of stratified signs but is configured as a natural absolute, and the fluid and symbolic space of vegetation that is defined as a figure in the surrounding background.The representation begins by palm drawing, it is, in fact, the measure of the oasis and its representation contains sacredness and symbolis. It is also a point of union between the world of forms and the world of the spirit.
Keywords: survey; landscape representation; vision; image; desert